Humanitarian Logistics Cross-Sector Cooperation in Disaster Relief Management - Cozzolino, Alessandra; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Following the recent dramatic rise in both natural and man-made disasters, humanitarian logistics has received increasing interest from both logistics researchers and practitioners. Provided that logistics operations in the emergency response are effective and efficient, the impact of disasters on affected populations can be drastically reduced. Relief operations involve many different actors operating in complex relationships so as to effectively and efficiently meet the various challenges of preparing for and responding to disasters. In some very recent studies, inter-organizational interactions have emerged among these various actors as an interesting area of development. More research would seem to be required to move from inter-agency coordination to cross-sector cooperation among humanitarian organizations and companies, with a special focus on logistics companies. This book focuses on one specific open question: in logistics and supply chain management, what are the cross-learning opportunities for both the businesses and humanitarian organizations that cooperate in disaster relief through partnership agreements? In terms of the available academic literature and management practice, this subject is still a poorly explored research area, and so the present study is one of the first attempts to thoroughly investigate the issue.
Introduction -- Humanitarian Logistics and Supply Chain Management -- Humanitarian Supply Chain Relationships: Working Together to Meet the Challenge of Preparing for and Responding to Disasters -- Emblematic Example of Strategic Cross-Sector Partnership: Logistics Emergency Teams.
Keywords: Economics; Development Economics; Economics/Management Science; Production/Logistics/Supply Chain Management; Non-Profit Enterprises/Corporate Social Responsibility; Development Economics